The Effect of Work Environment and Work Motivation on Employee Work Discipline at the Library and Archives Office of Central Tapanuli Regency - Tanjung, Rendy Putra Efendi; Panggabean, Sri Ayu Arta (Devitara Innovations, 2026)
This study aims to determine the effect of the work environment and work motivation on employee work discipline at the Library and Archives Office of Central Tapanuli Regency. The research method used is a quantitative method with a survey approach through the distribution of questionnaires to employees as respondents. Data analysis was carried out through validity tests, reliability tests, and classical assumption tests including normality, heteroscedasticity, and multicollinearity tests, as well as multiple linear regression analysis, correlation coefficient, coefficient of determination, t-test, and F-test. The results showed that all research instruments were valid and reliable and met the classical assumption requirements. The regression analysis produced the equation , indicating that the work environment has a negative effect on work discipline, while work motivation has a positive effect. However, based on the t-test results, both the work environment and work motivation partially have no significant effect on employee work discipline. Furthermore, the F-test results indicate that simultaneously the two independent variables also do not have a significant effect on work discipline. The coefficient of determination value of 16.2% indicates that work discipline can be explained by the work environment and work motivation variables by 16.2%, while the remaining 83.8% is influenced by other variables outside the research model.